ANALISIS PENERAPAN SISTEM PENGENDALIAN MANAJEMEN TERHADAP PRODUKTIVITAS DAN PENGGAJIAN PERUSAHAAN PADA MASA PANDEMI - Nadio Prakasila Prakasila (Universitas Sains dan Teknologi Komputer, 2021)
During this pandemic period, many companies have experienced a decline in performance in any aspect, but many companies are also able to maintain their performance even during the current pandemic from the many activities within the company that we do not know how to maintain their performance. The purpose of this study was to find out how to implement a management control system for company productivity and payroll during the pandemic. This study uses a descriptive qualitative method with the data used is primary data. Conclusion From the results and discussion above For the control system at the company CV. TRIO CIPTA has a control system with a new strategy that is more suitable to be applied during this pandemic so that the company that produces this RO machine can survive during this pandemic. Productivity at this company also experienced a very rapid increase.